Base de conhecimento docente em educação a distância: um estudo sobre educação musical - Corrêa, André Garcia (2013)
This research focuses on the particularities of teachers knowledge in Musical Education in the distance education modality, as well as the teachers adaptations to teach pratical music contente virtually. The investigation question was: What are the specificities and pedagogical adaptations of teachers knowledge related to the pratice of Musical Education in distance education? The specific goals of our work were: To characterize the virtual teacher s profile in the Musical Education course at the Federal University of São Carlos; (2) To identify how the investigated subjects learn to teach in distance education; (3) To point the investigated subject s possible adaptations and methodological inovations to teach music in distance education; and (4) to describe the subjects perception of how the teaching music process interaction in distance education occur. The research is descriptive and of a qualitative nature. The methodological procedures to collect the data were: a) the use of online surveys with objective and essay questions. The survey was also used to select subjects for the interviews; and b) semi-structered face to face interviews with pre-determined questions to gather deeper data and fill in the gaps lef by the survey. The theoretical referential used to analyze the gathered data contemplates distance education (Moore e Kearsley, Belloni, Mill, etc.), teacher s formation (Shulman, Tardif, Perrenoud, Mizukami, etc.) and recente scientific productions in musical education in distance education (Galizia, Krüger, Gohn, Carvalho, etc.). Regarding the the teacher knowledge specifities of the musical education virtual teacher found by our investigation, the virtual music teacher perceives him/herself as a coordinator for the virtual tutors team, as the responsible for the course s planning and the indirect interaction with the students knowledge construction. In his/her profile we found some formal pedagogical knowledge and also some formal knowledge about distance education with a considerable amount of experience in face to face education. However, the virtual music teacher depends for the most part on the reflexion upon his/her own practice to (re)build the specific knowledge for teaching music in distance education. The investigated subjects, for the most part, see the student as the key figure of the teaching-learning process in distance education. They see limitations in distance education, but also recognize advantages in the modality when comparing it to face to face education. The knowledge built by the investigated subjects by their own practices in distance education is about mastering Digital Technologies of information and communication and about virtual interaction.